What is the risk of urinary tract infection in children with antenatally presenting dilating vesico-ureteric reflux?. Issue 2 (April 2015) - Evans, Kathryn; Asimakadou, Maria; Nwankwo, Oluchi; Desai, Divyesh; Cherian, Abraham; Mushtaq, Imran; Cuckow, Peter; Duffy, Patrick; Smeulders, Naima
Summary Introduction The incidence of recurrent urinary tract infection (UTI) in children with primary vesico-ureteric reflux (VUR) presenting symptomatically is well documented. The risk of UTI in asymptomatic primary VUR diagnosed on investigation of antenatal hydronephrosis (ANH) is less clear. Paradoxically, several previous studies have suggested a lower risk (1–25%). We ascertain the incidence of UTI amongst antenatally-presenting primary VUR and explore risk factors. Study design All patients <16 years managed for primary VUR between 1997 and 2013 were retrospectively reviewed. Patients were identified by searching 'VUR, vesicoureteric reflux' and 'vesico' in the clinical database. Sex, follow up, antibiotic prophylaxis, age at UTI, grade of VUR, radioisotope imaging findings (CRN-congenital reflux nephropathy, NRD-new renal defects), evidence of bladder dysfunction, surgical intervention and resolution were recorded. UTI diagnosis was based on positive urine culture with symptoms including fever. SPSS statistical package and Pearson's Chi-squared test were used to explore significance. Results Of 308 patients with primary VUR aged <16 years treated, 242 were diagnosed following presentation with UTI. The remaining 66 (21%) were initially asymptomatic, and VUR was diagnosed on investigation of ANH. All were given prophylaxis from birth. Six months to 16years (median 6years) follow-up was available for 54 (42 males, 12 females). All but two patients had grade III-V VUR (96%), bilaterally in 41 (76%). CRN was evident in 30 (56%; all male) and bladder dysfunction in 12 (22%; 10 males). Twenty-eight patients (52%) developed a UTI. The risk of UTI was 58% in girls, 33% in boys without CRN and 57% in boys with CRN (p = 0.17). Bladder dysfunction was a significant risk factor for UTI (p = 0.03). All 8 (15%; 7 males) with NRD had had a UTI. A single UTI appeared responsible for the majority of NRD (6/8; 75%). UTI occurred in 6/27 (22%) boys after circumcision compared to 17/25 (68%) prior/without circumcision (p < 0.05). <table-wrap id="tbl" position="anchor"> Table <thead> Males UTI<break />21 No UTI<break />21 Total<break />42 </thead> Bladder dysfunction 8 (80%) 2 10 No bladder dysfunction 13 (40%) 19 32 </table-wrap> Conclusions The incidence of UTI in VUR detected after presentation with ANH was 52%. CRN and bladder dysfunction were risk factors for developing a UTI. Circumcision appears to significantly reduce the risk of infection. Antenatal presentation of primary VUR does not carry a reduced risk of UTI. A single UTI, in half before the age of six months, seemed responsible for the majority of NRD. In boys, the highest risk of UTI is in the first few months of infancy, despite antibiotic prophylaxis, and other interventions, particularly circumcision, should therefore be considered as early as possible.